Understanding of HLA-conferred susceptibility to chronic hepatitis B infection requires HLA genotyping-based association analysis - Nishida, Nao (Sci Rep, 2016)
Associations of variants located in the HLA class II region with chronic hepatitis B (CHB) infection have been identified in Asian populations. Here, HLA imputation method was applied to determine HLA alleles using genome-wide SNP typing data of 1,975 Japanese individuals (1,033 HBV patients and 942 healthy controls). Together with data of an additional 1,481 Japanese healthy controls, association tests of six HLA loci including HLA-A, C, B, DRB1, DQB1, and DPB1, were performed. Although the strongest association was detected at a SNP located in the HLA-DP locus in a SNP-based GWAS using data from the 1,975 Japanese individuals, HLA genotyping-based analysis identified DQB1*06:01 as having the strongest association, showing a greater association with CHB susceptibility (OR = 1.76, P = 6.57 × 10(−18)) than any one of five HLA-DPB1 alleles that were previously reported as CHB susceptibility alleles. Moreover, HLA haplotype analysis showed that, among the five previously reported HLA-DPB1 susceptibility and protective alleles, the association of two DPB1 alleles (DPB1*09:01, and *04:01) had come from linkage disequilibrium with HLA-DR-DQ haplotypes, DRB1*15:02-DQB1*06:01 and DRB1*13:02-DQB1*06:04, respectively. The present study showed an example that SNP-based GWAS does not necessarily detect the primary susceptibility locus in the HLA region.